1970
DOI: 10.1042/cs0380073
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Blood Flow and Splanchnic Haemodynamics in Blood Dyscrasia and other Splenomegalies

Abstract: 1. Splenic blood flow and splanchnic haemodynamics have been studied in twenty patients with splenomegaly due to blood dyscrasia or diseases involving the reticuloendothelial system. Thirteen of these patients had portal hypertension, three had abdominal collaterals on arteriovenography and one oesophageal varices. 2. Total spleen blood flow was increased in all with values up to 1550 ml/min, and associated with this liver blood flows increased up to 2·61 1 min−1 m−2. In four patients the cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…It is further more noteworthy that gastro-intestinal tract bleeding from varices may occur in these patients, as a result of which splenectomy has been advocated [Silverstein et al, 1973]. It is, however, recognised that proper as sessment of splanchnic haemodynamics and asso ciated hepatic structural changes should be carefully defined in planning the best surgical procedure to correct the portal hypertension [Blendis et al, 1970;Gomes et al, 1967], The importance of adequate pre operative investigation is illustrated by this case re port in which previously silent venous thrombosis ob structed the splenic and portal vessels and where con servative management rather than splenectomy or shunt surgery was the appropriate form of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is further more noteworthy that gastro-intestinal tract bleeding from varices may occur in these patients, as a result of which splenectomy has been advocated [Silverstein et al, 1973]. It is, however, recognised that proper as sessment of splanchnic haemodynamics and asso ciated hepatic structural changes should be carefully defined in planning the best surgical procedure to correct the portal hypertension [Blendis et al, 1970;Gomes et al, 1967], The importance of adequate pre operative investigation is illustrated by this case re port in which previously silent venous thrombosis ob structed the splenic and portal vessels and where con servative management rather than splenectomy or shunt surgery was the appropriate form of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in portal flow itself may explain PH. In fact, few cases of PH in myelofibrosis patients secondary to increased splenic and/or portal flow with minimal hematopoiesis have been reported [20,21] . On the other hand, Sikuler et al [22] experimentally demonstrated that in the absence of structural alteration of the liver, PH does not develop as a consequence of an increased portal flow.…”
Section: Discussionmentioning
confidence: 99%
“…5 Splenomegaly is one of the major characteristics of long lasting portal hypertension, and in LSPH splenomegaly is more expressed than in liver cirrhosis. 6 In our paper we presented a case of a male patient with history of repetitive chronic pancreatitis exacerbations due to aethylic etiology. With continuous, long lasting alcohol consumption he developed chronic pancreatitis and consequently by repetitive exacerbations he developed fixed bulbostenosis and gastric varices due to splenic vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%